Thermosipho spp. Immune System Differences Affect Variation in Genome Size and Geographical Distributions. (15th September 2018) - Haverkamp, Thomas H A; Geslin, Claire; Lossouarn, Julien; Podosokorskaya, Olga A; Kublanov, Ilya; Nesbø, Camilla L
Abstract: Thermosipho species inhabit thermal environments such as marine hydrothermal vents, petroleum reservoirs, and terrestrial hot springs . A 16S rRNA phylogeny of available Thermosipho spp. sequences suggested habitat specialists adapted to living in hydrothermal vents only, and habitat generalists inhabiting oil reservoirs, hydrothermal vents, and hotsprings. Comparative genomics of 15 Thermosipho genomes separated them into three distinct species with different habitat distributions: The widely distributed T. africanus and the more specialized, T. melanesiensis and T. affectus . Moreover, the species can be differentiated on the basis of genome size (GS), genome content, and immune system composition. For instance, the T. africanus genomes are largest and contained the most carbohydrate metabolism genes, which could explain why these isolates were obtained from ecologically more divergent habitats. Nonetheless, all the Thermosipho genomes, like other Thermotogae genomes, show evidence of genome streamlining. GS differences between the species could further be correlated to differences in defense capacities against foreign DNA, which influence recombination via HGT. The smallest genomes are found in T. affectus that contain both CRISPR-cas Type I and III systems, but no RM system genes. We suggest that this has caused these genomes to be almost devoid of mobile elements, contrasting the two other species genomes that contain a higher abundance of mobile elements combined with different immune system configurations. Taken together, the comparative genomic analyses of Thermosipho spp. revealed genetic variation allowing habitat differentiation within the genus as well as differentiation with respect to invading mobile DNA.